2017
DOI: 10.2337/cd15-0030
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Is Devastating, and Insulin Is a Death Sentence: Provider Perspectives of Diabetes Self-Management in Arab-American Patients

Abstract: IN BRIEF The purpose of this qualitative study was to examine providers’ perspectives on cultural barriers and facilitators to diabetes self-management (DSM) in Arab Americans to identify factors to enhance DSM education in the Arab-American community. The main barriers to DSM from the providers’ perspective were the disease itself and patients’ denial or refusal to recognize it, reflecting the stigma of the disease. Cultural aspects also included overlapping themes that both facilitated and presented barriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…A similar result was found in Palestinian children with T1DM, who perceived diabetes as a stigmatizing condition that spoiled their identity as a healthy individual, making them feel like an outsider and not a normal person (Elissa et al, 2016). A study performed in a U.S. Arab American community found that individuals often viewed diabetes as a weakness or breakdown (DiZazzo-Miller et al, 2017).…”
Section: Sicksupporting
confidence: 52%
See 2 more Smart Citations
“…A similar result was found in Palestinian children with T1DM, who perceived diabetes as a stigmatizing condition that spoiled their identity as a healthy individual, making them feel like an outsider and not a normal person (Elissa et al, 2016). A study performed in a U.S. Arab American community found that individuals often viewed diabetes as a weakness or breakdown (DiZazzo-Miller et al, 2017).…”
Section: Sicksupporting
confidence: 52%
“…A similar result was found in Palestinian children with T1DM, who perceived diabetes as a stigmatizing condition that spoiled their identity as a healthy individual, making them feel like an outsider and not a normal person (Elissa et al., ). A study performed in a U.S. Arab American community found that individuals often viewed diabetes as a weakness or breakdown (DiZazzo‐Miller et al., ). Indian mothers of children with diabetes experienced diabetes‐related stigma when other people labelled their child as a “sick kid” (Verloo, Meenakumari, Abraham, & Malarvizhi, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the home environment, the data revealed the heightened levels of temptations participants faced on a regular basis and the overt ridicule and sabotage they experienced as they did their best to engage in the recommended behaviour. Such stigma and ridicule thus increase the likelihood that the requisite self-care behaviours for remission may be compromised [40, 41]. Furthermore, consistent with previous research, the challenges participants experienced making the requisite dietary changes were intensified if their family members were not necessarily willing to follow their diet regimen and at the congregate meal sites they continued eating their regular meals [16, 35, 39, 42, 43].…”
Section: Findings In Contextmentioning
confidence: 78%
“… 16. For further discussion on race and diabetes, consider Bacon et al (2017), DiZazzo-Miller et al (2017), Hayashino et al (2018), and Reitblat et al (2016). Note (a) there is no such thing as “perceived” racism, (b) each of these articles discuss diabetes from the provider perspective, without patient voices included in the article-formations, and finally, (c) both previous points indicate a general lack of trust and respect in people’s lived experiences, expertise, and embodiment. …”
mentioning
confidence: 99%